The Role of Online Puzzle Games as Educational Tools for Children with Stunting Symptoms - Utami, Wiwik; Dioso, Regidor III; Hassan, Datin Dr. Hafizah Che; Afandi , Agus Ari; Huda, Akhmad; Nuryanti, Titik (Qualitative and Quantitative Research Center, 2024)
Stunting risks children's physical, mental, and cognitive development, leading to long-term impairments, significantly affecting their overall growth, learning abilities, and future potential. Online puzzle games allow children to practice concentration and hand-eye coordination through interactive challenges that stimulate children's creativity and memory. This study aims to assess the effect of educational online puzzle games on the development of preschool children with stunting symptoms. A pre-experimental design with a pretest-posttest approach was used, involving 52 children aged 3-6 years diagnosed with stunting symptoms. The children's development was measured using the Denver II screening tool. Data were processed using editing, coding, scoring, and tabulation, followed by crosstab statistical analysis. The results showed that 50% of respondents had abnormal development before playing the online puzzle game, while 65.4% had normal development afterwards. A significant improvement was observed, as indicated by the rejection of H0, suggesting that online puzzle games positively affect the development of preschool children with stunting symptoms. The study concludes that online puzzle games can stimulate the development of children with stunting symptoms. It is recommended that families regularly provide educational games to enhance the development of children affected by stunting symptoms. Future research should consider larger sample sizes and explore the long-term effects of such interventions.